MERN projects for beginners : create five social web apps using MongoDB, Express.js, React, and Node - Biswas, Nabendu (Apress, 2021)
Learn how to use the MERN stack (MongoDB, Express.js, React, and Node) to build five fully functioning web apps for dating, video sharing, messaging, and social media. While creating these web apps, youll learn key development concepts including how to use React hooks, Redux, MongoDB, Express, Heroku, Firebase, Material UI, and Google authentication. By expanding your portfolio with the projects you create, you will be well equipped as front-end developer. You will first create a dating site with a swiping feature and chat functionality. You will then build a video sharing app with videos displaying vertically. Next, you will learn to build an awesome messaging web app. Users will be able to chat in real time, as well as log in to their account using Google authentication. You will also create a photo sharing app and social media web apps with the ability to post images with captions and log in using email and password authentication. Most MERN tutorials out there today cover basic web apps but it is capable of so much more learn how to use this stack to its full potential and build projects that can be converted into full scaled start-ups with additional features. You will: Work with React hooks and React router Examine powerful MongoDB services for easy to use and setup Create routes using Node and host on Heroku Study different authentication techniques Deploy all sites using simple Firebase hosting Use the powerful React ecosystem to add functionalities to your apps.